Shear strength of hollow circular sections - F. O. Queiroz Junior; B. Horowitz (Revista IBRACON de Estruturas e Materiais)
ABSTRACT The number of buildings higher than 30 floors has shown remarkable growth; many of them are supported on foundations of hollow circular piles. This increasing of height of constructions causes an increment of the shear stresses that are transmitted to their foundations, however these elements are more shear critical due to the hollow core. Most of the existing codes are based on shear models for rectangular sections, and guidelines for assessment of shear strength of members with hollow circular cross sections are practically non-existent. This study evaluates, on a comparative basis, the shear strength of elements with hollow circular cross sections, obtained from experimental tests, with values computed using the Canadian Code (CSA A23.3) and using a proposed simple procedure based on the Brazilian standard (NBR 6118).